Self Healing with Positive Activities to Maintain Mental Health during the 3rd Wave Covid-19 Pandemic in Youth in Mts.1 Regency of Gorontalo - Nur Uyuun I. Biahimo; Firmawati Firmawati (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This study aims to find out the procedures for handling Covid-19 at MTs. State 1, Gorontalo Regency. Schools are asked to adhere to strict health protocols in an effort to break the chain of COVID-19. The implementation of this Community Service activity will be held on February 23, 2022 WITA. The stages of achieving the target results are described according to the order of implementation methods with some modifications according to field conditions. The results achieved with this activity are 42 students who are willing to take part in Community Service and according to reports on evidence of activities carried out. MTs party. The State 1 of Gorontalo Regency expressed his gratitude. In conclusion, increasing knowledge to students on how to maintain mental health in the covid-19 pandemic by using the self-healing method with positive activities. Increasing students' skills on how to maintain mental health in the era of the COVID-19 pandemic by using the self-healing method with positive activities. The collaboration of Nurses Class XII and lecturer service is an activity that benefits both the community and the campus.